The chromosome-scale genome reveals the evolution and diversification after the recent tetraploidization event in tea plant. (1st May 2020) - Chen, Jie-Dan; Zheng, Chao; Ma, Jian-Qiang; Jiang, Chen-Kai; Ercisli, Sezai; Yao, Ming-Zhe; Chen, Liang
Abstract: Tea is one of the most popular nonalcoholic beverages due to its characteristic secondary metabolites with numerous health benefits. Although two draft genomes of tea plant ( Camellia sinensis ) have been published recently, the lack of chromosome-scale assembly hampers the understanding of the fundamental genomic architecture of tea plant and potential improvement. Here, we performed a genome-wide chromosome conformation capture technique (Hi-C) to obtain a chromosome-scale assembly based on the draft genome of C. sinensis var. sinensis and successfully ordered 2984.7 Mb (94.7%) scaffolds into 15 chromosomes. The scaffold N50 of the improved genome was 218.1 Mb, 157-fold higher than that of the draft genome. Collinearity comparison of genome sequences and two genetic maps validated the high contiguity and accuracy of the chromosome-scale assembly. We clarified that only one Camellia recent tetraploidization event (CRT, 58.9–61.7 million years ago (Mya)) occurred after the core-eudicot common hexaploidization event (146.6–152.7 Mya). Meanwhile, 9243 genes (28.6%) occurred in tandem duplication, and most of these expanded after the CRT event. These gene duplicates increased functionally divergent genes that play important roles in tea-specific biosynthesis or stress response. Sixty-four catechin- and caffeine-related quantitative trait loci (QTLs) were anchored to chromosome assembly. Of these, two catechin-related QTL hotspots were derived from the CRT event, which illustrated that polyploidy has played a dramatic role in the diversification of tea germplasms. The availability of a chromosome-scale genome of tea plant holds great promise for the understanding of genome evolution and the discovery of novel genes contributing to agronomically beneficial traits in future breeding programs.